The Role Of The Importance Of Financial Literation For Generation Millennialdi Era Digital - Rilsha Rilsha; Fachrun Nissa (Proceeding International Seminar of Islamic Studies, 2019)
Advances in technology in the digital age make all aspects of life complex so that it requires humans to continue to develop and strive to meet their needs. One of the demands that must be developed by people in the centuries to be able to compete in basic literacy capabilities, one still occupies a relatively low position among other countries. The phenomenon found today is that people tend to engage in consumptive behavior because of the easier access to make transactions online, this is especially true for adolescents at the high school age. Based on the 2016 survey on the level of financial literacy, it shows that students at the student level have a percentage of 23,4% and based on age 15-17 years with a percentage of 5,2%. The low level of financial literacy at the learning level is due to the lack of knowledge among adolescents about the importance of financial management for the future. This study aims to determine the importance of financial literacy among teenage students in the digital age. The research method is carried out by studying literature by examining previous and qualitative research. Based on this research it is known that financial literacy education is important to be given to teenagers in the current digital era as a form of self-control to realize a financially literate future which is financial literacy. The 2015 World Bank survey results on financial literacy show Indonesia.